2013
DOI: 10.1590/s1809-29502013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Análise da flexibilidade segmentar e prevalência de lesões no futebol segundo faixa etária

Abstract: Retrações musculares têm apresentado relações com má postura e Lesões Desportivas (LD) em jogadores de futebol jovens e adultos. Este estudo teve por objetivo avaliar a flexibilidade articular, extensibilidade muscular e prevalência de LD em praticantes de futebol, relacionando-as com a faixa etária. A casuística integrou 170 participantes do sexo masculino, procedentes das equipes de base profissionalizante e profissional de um clube desportivo de Campo Grande (MS). Os participantes foram distribuídos em três… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
1
7
0
4
Order By: Relevance
“…Our findings are also consistent with the study published by Kluitenberg et al, 38 which included 1,696 male and female participants; 33.6% of the subjects reported injuries. The prevalence rate in our study is also in line with the ranges proposed in the systematic reviews published by Van Gent et al 39 (19.4% to 79.3%) and Von der Worp et al 40 (20.6% to 79.3%). In soccer, the prevalence of injuries was 28.23% for teams of professional juvenile athletes, 41 whereas the prevalence of musculoskeletal injuries in crossfit athletes with an average age of 32 years was 30.2%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are also consistent with the study published by Kluitenberg et al, 38 which included 1,696 male and female participants; 33.6% of the subjects reported injuries. The prevalence rate in our study is also in line with the ranges proposed in the systematic reviews published by Van Gent et al 39 (19.4% to 79.3%) and Von der Worp et al 40 (20.6% to 79.3%). In soccer, the prevalence of injuries was 28.23% for teams of professional juvenile athletes, 41 whereas the prevalence of musculoskeletal injuries in crossfit athletes with an average age of 32 years was 30.2%.…”
Section: Discussionsupporting
confidence: 93%
“…48 Additionally, the risk profile in men could be also related to the higher running speed and greater distance of running per week. 40,49 Concerning the anatomical region, we observed that the knee is the most affected site of injury, with a prevalence of 33.5%. A similar value was reported by Van Poppel et al 45 (31.1%) for knee injuries in 713 subjects.…”
Section: Participantsmentioning
confidence: 82%
See 1 more Smart Citation
“…Although diverse, requirements of these positions include interceptions during matches' dynamic circumstances, characterized by numerical handicaps and demands for defense actions in order to recover the ball [33]. Hence, important contractile demands on hip muscles have been associated with frequent muscle retraction among soccer players [21,34], contributing to excessive back lordosis and hip misalignment [35]. Accentuated prevalence of muscle injuries in back sites in advanced midfielders (Table 3) can derive from repetitive functional overload and hip muscle retractions.…”
Section: Discussionmentioning
confidence: 99%
“…Another essential physical attribute in the performance of sports gestures is flexibility, which undergoes adaptations with the sport modality 14 . Achieving the optimal flexibility level positively affects joint range, strength, and speed of movement during exercises, making them easier to be performed, decreasing total energy expenditure because the range of motion is efficient for the performance of specific gestures [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%